A novel classification scheme to decline the mortality rate among women due to breast tumor. Issue 2 (16th November 2017) - Mughal, Bushra; Sharif, Muhammad; Muhammad, Nazeer; Saba, Tanzila
Abstract: Early screening of skeptical masses or breast carcinomas in mammograms is supposed to decline the mortality rate among women. This amount can be decreased more on development of the computer‐aided diagnosis with reduction of false suppositions in medical informatics. Our aim is to provide a robust tumor detection system for accurate classification of breast masses using normal, abnormal, benign, or malignant classes. The breast carcinomas are classified on the basis of observed classes. This is highly dependent on feature extraction process. In propose work, a novel algorithm for classification based on the combination of top Hat transformation and gray level co‐occurrence matrix with back propagation neural network. The aim of this study is to present a robust classification model for automated diagnosis of the breast tumor with reduction of false assumptions in medical informatics. The proposed method is verified on two datasets MIAS and DDSM. It is observed that rate of false positives decreased by the proposed method to improve the performance of classification, efficiently. Abstract : An automated system for the classification of breast abnormalities patterns. Segmentation free classification scheme by calculating a mesh of salient descriptors.